Design and manufacturing method of diaphragm for high-safety quick-charge type lithium battery
By using mesogenic anatase TiO2 and MoS2 nanomaterials in lithium-ion batteries to modify the PVDF membrane, combined with the expansion stress of the silicon-based negative electrode, the risk of lithium-ion batteries is suppressed, and the safety and performance problems of lithium-ion batteries are solved during fast charging. Significantly improves battery safety and cycle life.
Patent Information
- Application Number
- CN202411296213.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-18
AI Technical Summary
Lithium-ion power batteries are prone to lithium-ion assays during fast charging, which affects battery performance and safety. In the prior art, for example, the piezoelectric capacity of flexible piezoelectric polyvinylidene fluoride (PVDF) diaphragms is limited, making it difficult to effectively suppress lithium-ion evolution. risk.
The PVDF separator is modified with mesogenic anatase TiO2 and MoS2 nanomaterials. By using the stress generated by the expansion of silicon-based negative electrodes in silicon-based lithium-ion batteries, the risk of lithium-ion analysis is suppressed and polarization is carried out through polarization treatment. Improve the piezoelectric properties of the diaphragm.
It significantly improves the safety and service life of lithium-ion batteries, extends the lithium-ion inflection point, reduces the safety risks under fast charging, and improves the cycle life of lithium-ion batteries.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion power batteries for electric aviation, and in particular to a design and manufacturing method of a diaphragm for a high-safety fast-charging lithium battery. Background Art
[0002] As a representative of new productivity, low-altitude economy is triggering fierce competition around the world. The core of this strategic emerging industry lies in electric low-altitude aircraft, especially electric vertical take-off and landing aircraft (eVTOL). eVTOL has become the focus of attention at home and abroad for its high safety, low cost, low noise and intelligent characteristics.
[0003] The development of eVTOL has not only promoted the widespread application of lithium battery technology, but also provided a broad space for the development of next-generation battery technology. However, eVTOL has more stringent performance requirements for lithium batteries, especially in terms of high specific energy and high safety. High specific energy lithium-ion power batteries have become the main power source for eVTOL due to their high energy density, small size, and light weight.
[0004] However, during fast charging, lithium deposition is prone to occur on the negative electrode surface of lithium-ion power batteries, which not only affects the performance of the battery, but may also pose a serious threat to the safety and reliability of the battery. Using piezoelectric materials to generate reverse overpotential during the operation of lithium batteries to weaken the driving force of lithium ion nucleation, deposition, diffusion and deposition has become an important technical method to inhibit fast charging and lithium deposition due to its simple operation, low cost and good effect.
[0005] For example, in the invention patent application with application number 202311712605.9, a diaphragm for lithium-ion batteries and its preparation method and application are proposed, which uses flexible piezoelectric polyvinylidene fluoride (PVDF) as an innovative method of lithium-ion battery diaphragm. Through the application of this diaphragm, it aims to reduce the risk of metal lithium precipitation on the surface during charging, thereby improving the safety of the battery and its compatibility with the lithium metal battery system. However, the limitation of this technical solution is that due to the relatively single component of the PVDF diaphragm, its piezoelectric ability is limited, which will affect the performance of the diaphragm in the battery. Summary of the invention
[0006] The purpose of the present invention is to provide a design and manufacturing method for a high-safety fast-charging lithium battery diaphragm, which uses mesogenic rutile TiO2 and MoS2 nanomaterials to modify the PVDF diaphragm, significantly improving the piezoelectric properties of the PVDF membrane, combining the stress generated by the expansion of the silicon-based negative electrode in the silicon-based lithium-ion battery, and generating a certain reverse overpotential at the interface between the negative electrode and the diaphragm, effectively suppressing the risk of lithium plating at the negative electrode interface under fast charging, and significantly improving the safety and service life of the battery.
[0007] The technical solution adopted by the present invention to solve the above technical problems is:
[0008] A method for manufacturing a diaphragm for a high-safety fast-charging lithium battery comprises the following steps: adding mesomorphous anatase titanium dioxide powder, MX2 semiconductor nanomaterial and PVDF in a molar ratio of 0.3-0.7:0.2-0.5:1.5-1.9 to a polar solvent, stirring at room temperature and ultrasonically treating the mixture, casting the mixture on an ITO conductive glass substrate, and then vacuum drying the mixture at 60°C-80°C to form a TiO2-MX2-PVDF composite film, then spraying gold on the surface of the film, and finally polarizing the gold-sprayed TiO2-MX2-PVDF composite film, applying a voltage in the range of 3V-9V and a frequency of 3mS-5mS, to prepare a TiO2-MX2-PVDF composite diaphragm mainly composed of β phase.
[0009] Preferably, M in the MX2-type semiconductor nanomaterial is a transition metal element W or Mo, and X is one of Te, Se, and S.
[0010] Preferably, the thickness of the TiO2-MX2-PVDF composite film after vacuum drying is 1 μm-15 μm, and the thickness of the gold spraying is 5 nm-10 nm.
[0011] Preferably, the polar solvent includes one of dimethylformamide DMF, dimethylacetamide DMA, hexamethylphosphoramide, trifluoroacetic acid, tetramethylethylenediamine, pyridine and dimethyl sulfoxide.
[0012] Preferably, the mesocrystalline anatase titanium dioxide powder is prepared by the following method: dissolving a titanium source in a 1 mol / L-3 mol / L hydrochloric acid solution, with a volume ratio of the titanium source to the hydrochloric acid solution of 1-3:4-10, stirring at 40°C-100°C for 40h-60h, centrifuging to obtain a white product, washing the white product with deionized water to remove residual inorganic ions, and then vacuum drying the white product at 80°C-120°C for 12h-36h, and finally calcining in air at 400°C-500°C for 12h-24h to obtain a mesocrystalline anatase titanium dioxide powder.
[0013] Preferably, the titanium source includes at least one of titanocene dichloride, tetraisopropoxytitanium, tetrabutyl titanate, titanium citrate and titanium tetrachloride.
[0014] Preferably, the MX2 type semiconductor nanomaterial is MoS2 nanomaterial, which is prepared by a solvothermal method: ammonium molybdate or ammonium heptamolybdate tetrahydrate and an organic acid are added to deionized water in a molar ratio of 0.5-1.5:4-7, and magnetic stirring is performed at room temperature until dissolved, and stirring is continued at 110-140°C. The white suspension is continuously stirred and refluxed, and ammonia water is added to adjust the pH value to 3.5-4.5, and then one of ammonium polysulfide, thiourea, and ammonium sulfide is added dropwise to the solution, and finally the solution is transferred to a stainless steel autoclave, the autoclave is maintained at 185°C-200°C for a period of time, naturally cooled to room temperature, and the solution is centrifuged to obtain a black precipitate MoS2, which is rinsed with acetone and deionized water in turn to remove residues.
[0015] Preferably, the molar ratio of ammonium molybdate to ammonium polysulfide is 0.5-1.5:0.7-1.9.
[0016] Preferably, the organic acid is one of gluconic acid, citric acid, malic acid and lactic acid.
[0017] A high-safety fast-charging lithium battery comprises a diaphragm prepared by the above method.
[0018] Compared with the prior art, the advantages of the present invention are:
[0019] 1. The present invention significantly enhances the piezoelectric properties of the PVDF diaphragm by introducing a TiO2-MoS2 two-component nucleating additive, and utilizes the expansion stress of the silicon-based negative electrode to generate a reverse overpotential to weaken the probability of lithium precipitation at the interface between the negative electrode and the diaphragm. The lithium precipitation inflection point appears later. Compared with conventional diaphragms, the fast-charging cycle life of lithium-ion batteries is increased by more than 200%, significantly reducing the safety risks of lithium-ion batteries under fast charging. At the same time, the mesocrystal rutile titanium dioxide material provides more lithium storage sites, further improving the cycle life of the battery. The method of the present invention is also applicable to the performance improvement of high-energy-density metal lithium batteries, and provides a technical reference for the development of fast-charging lithium-ion power batteries in fields such as electric aviation.
[0020] 2. Through the use of intermolecular interactions and nanofillers, PVDF can be effectively promoted to form a β-phase structure with special properties. Intermolecular bonding from different molecules or surface functional groups will promote the β-phase formation of PVDF and its copolymers. The polar interaction between PVDF and the polar solvent dimethylformamide leads to the formation of β-phase through crystallization during solvent evaporation, while mesogenic anatase TiO2 and MoS2 nanofillers further optimize the interface and promote the preferential orientation of CH2 / –CF2 dipoles in the direction perpendicular to the PVDF chain axis, thereby generating more β-phase-PVDF.
[0021] 3. Strain concentration occurs at the interface between mesocrystalline rutile TiO2 and MoS2 nanofillers. The coordinated control of the surface and interface between the two not only promotes the generation of local β phase in the matrix, but also effectively improves the strain transmission effect of nanofillers with high piezoelectric sensitivity, significantly enhancing the piezoelectric properties of TiO2-MoS2-PVDF composite film.
[0022] 4. Compared with other crystal forms, mesogenic anatase titanium dioxide has more lithium storage sites, which is beneficial to improve the lithium ion transmission performance in PVDF composite diaphragm and improve the fast charging performance of lithium ion batteries. DETAILED DESCRIPTION
[0023] The following will be described clearly and completely in conjunction with the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0024] Embodiment 1,
[0025] A high-safety fast-charging lithium battery comprises a positive electrode sheet, a negative electrode sheet and a separator.
[0026] The diaphragm is prepared by the following method: adding mesomorphous anatase titanium dioxide, MoS2 nanomaterials and PVDF in a molar ratio of 0.5:0.4:1.6 to dimethylformamide DMF, stirring magnetically at room temperature for 1.5 hours, then ultrasonically treated (55KHZ) for 35 minutes, casting the mixed solution on an ITO conductive glass substrate, and then placing it in an oven at 75°C and a vacuum degree of 0.07 standard atmospheric pressure for 30 hours to form a TiO2-MoS2-PVDF composite film, and then spraying gold on the surface of the film. Among them, the thickness of the TiO2-MoS2-PVDF composite film is 2μm, and the thickness of the sprayed gold is 9nm. Finally, the TiO2-MoS2-PVDF composite film after spraying gold is polarized, and the applied voltage range is 5V and the frequency is 4mS, and a TiO2-MoS2-PVDF composite film mainly composed of β phase is prepared.
[0027] The dimethylformamide DMF in this embodiment can be replaced by one of polar solvents such as dimethylacetamide DMA, hexamethylphosphoramide, trifluoroacetic acid, tetramethylethylenediamine, pyridine, dimethyl sulfoxide, etc.
[0028] Preparation of mesocrystalline anatase titanium dioxide powder: First, a certain amount of tetraisopropoxy titanium was dripped into 1.5 mol / L hydrochloric acid, where the volume ratio of isopropoxy titanium to hydrochloric acid was 1:3. Then, stirring was continued at 70°C for 52 hours, and a white product was obtained after centrifugation. The product was washed with deionized water 5 times to remove the residual non-polar ions. After the white product was vacuum dried at 110°C for 26 hours, it was sintered in air at 450°C for 20 hours to obtain mesocrystalline anatase titanium dioxide powder.
[0029] MoS2 nanomaterials were prepared by a simple and easy-to-operate solvothermal method: ammonium heptamolybdate tetrahydrate and gluconic acid were added to deionized water in a molar ratio of 1:5, and magnetically stirred at room temperature until dissolved. Stirring was continued at 130°C for 45 minutes, and the white suspension was continuously stirred and refluxed. Ammonia water was added to adjust the pH value to 3.6, and then ammonium polysulfide was added dropwise to the solution. The molar ratio of ammonium molybdate to ammonium polysulfide was 1:1.2. Finally, the solution was transferred to a stainless steel autoclave, the autoclave was kept at 190°C for 14 hours, and naturally cooled to room temperature. The solution was centrifuged to obtain a black precipitate MoS2, which was rinsed 3 times with acetone and deionized water respectively to remove the residue.
[0030] Preparation method of positive electrode sheet:
[0031] The positive electrode active material layered high-nickel ternary material (NCM811), the conductive agent single-walled carbon nanotubes, the binder PVDF and N-methylpyrrolidone (NMP) are put into a spherical tank in a mass ratio of 96:1.2:2.5:145, the ball-to-material ratio is 1.3:1, the grinding time is 55 minutes, and the mixed slurry is evenly coated on the aluminum current collector by a scraper method or a transfer coating method. The coating thickness is 110μm. After drying, rolling and punching, the positive electrode sheet is obtained.
[0032] Preparation method of negative electrode sheet:
[0033] Silicon carbon, artificial graphite, single-walled carbon nanotubes, binder PAA and deionized water are put into a ball mill at a mass ratio of 55:45:2:6:380, the ball-to-material ratio is 1.3:1, and the grinding time is 65 minutes. The mixed slurry is evenly coated on the copper current collector by a scraper method or a transfer coating method with a coating thickness of 85 μm. The negative electrode sheet is obtained after drying, rolling and punching.
[0034] The β-phase-based TiO2-MoS2-PVDF composite membrane prepared above is superimposed and composited with a conventional PP separator, and a lithium-ion battery is obtained after stacking, welding, packaging, liquid injection and chemical formation with positive and negative electrode sheets.
[0035] Embodiment 2,
[0036] A high-safety fast-charge lithium battery, which is different from Example 1 in that the diaphragm in the present application is prepared by the following method: adding mesomorphous rutile titanium dioxide, MoS2 nanomaterials and PVDF to dimethylacetamide DMA at a molar ratio of 0.7:0.2:1.9, magnetically stirring at room temperature for 2 hours, then ultrasonically treating (60KHZ) for 20 minutes, casting the mixed solution on an ITO conductive glass substrate, and then placing it in an oven at 80°C and a vacuum degree of 0.05 standard atmospheric pressure for 35 hours to form a TiO2-MoS2-PVDF composite film, and then spraying gold on the surface of the film. Among them, the thickness of the TiO2-MoS2-PVDF composite film is 1μm, and the thickness of the gold spraying is 5nm. Finally, the TiO2-MoS2-PVDF composite film after gold spraying is polarized, and the applied voltage range is 9V and the frequency is 5mS, to prepare a TiO2-MoS2-PVDF composite film mainly composed of β phase.
[0037] Embodiment 3,
[0038] A high-safety fast-charge lithium battery, which differs from Example 1 in that mesomorphous anatase titanium dioxide, MoS2 nanomaterials and PVDF are added to hexamethylphosphoramide in a molar ratio of 0.3:0.5:1.5, magnetically stirred at room temperature for 1 hour, then ultrasonically treated (40KHZ) for 40 minutes, the mixed solution is cast on an ITO conductive glass substrate, and then placed in an oven at 60°C and a vacuum degree of 0.2 standard atmospheric pressure for 25 hours to form a TiO2-MoS2-PVDF composite film, and then gold is sprayed on the surface of the film. Among them, the thickness of the TiO2-MoS2-PVDF composite film is 15μm, and the thickness of the gold spraying is 10nm. Finally, the TiO2-MoS2-PVDF composite film after gold spraying is polarized, and the applied voltage range is 3V and the frequency is 3mS, to prepare a TiO2-MoS2-PVDF composite film mainly composed of β phase.
[0039] Embodiment 4,
[0040] A high-safety fast-charging lithium battery, which differs from Example 1 in that, in the preparation process of MoS2 nanomaterials: ammonium molybdate and citric acid are added to deionized water at a molar ratio of 0.5:7, and magnetic stirring is performed at room temperature until dissolved, and stirring is continued at 110°C for 60 minutes. The white suspension is continuously stirred and refluxed, and ammonia water is added to adjust the pH value to 3.5, and then ammonium polysulfide is added dropwise to the solution, and the molar ratio of ammonium molybdate to ammonium polysulfide is 1.5:0.7. Finally, the solution is transferred to a stainless steel autoclave, the autoclave is maintained at 200°C for 12 hours, and naturally cooled to room temperature. The solution is centrifuged to obtain a black precipitate MoS2, and then rinsed with acetone and deionized water 3 times each to remove residues.
[0041] Embodiment 5,
[0042] A high-safety fast-charging lithium battery, which differs from Example 1 in that WS2 nanomaterials are used in the preparation process of the diaphragm.
[0043] Embodiment 6,
[0044] A high-safety fast-charging lithium battery, which differs from Example 1 in that WSe2 nanomaterials are used in the preparation process of the diaphragm.
[0045] Comparative Example 1
[0046] Compared with Example 1, mesocrystalline rutile titanium dioxide powder is used, and the specific preparation method of mesocrystalline rutile titanium dioxide powder is as follows: a certain amount of tetraisopropoxy titanium is dripped into 1.5 mol / L hydrochloric acid, wherein the volume ratio of isopropoxy titanium to hydrochloric acid is 1:3. Then continue stirring at 70°C for 52 hours, obtain a white product after centrifugation, and wash it with deionized water 5 times to remove residual non-polar ions. After the white product is vacuum dried at 110°C for 26 hours, continue to calcine at 550°C in air for 20 hours to obtain mesocrystalline rutile titanium dioxide powder.
[0047] Comparative Example 2
[0048] Compared with Example 1, the PVDF composite diaphragm in Comparative Example 2 does not add mesomorphous anatase titanium dioxide, and the other conditions are the same as those in Example 1.
[0049] Comparative Example 3
[0050] Compared with Example 1, the PVDF composite membrane in Comparative Example 3 does not add MoS2 nanomaterials, and the other conditions are the same as those in Example 1.
[0051] Comparative Example 4
[0052] Compared with Example 1, the PVDF composite membrane in Comparative Example 4 does not add MoS2 and titanium dioxide nanomaterials, and the other conditions are the same as those in Example 1.
[0053] Comparative Example 5
[0054] Compared with Example 1, the lithium ion battery in Comparative Example 5 only uses a conventional PP diaphragm without a PVDF composite diaphragm, and the other conditions are the same as those in Example 1.
[0055] Measurement of piezoelectric coefficient: The piezoelectric coefficient of PVDF was accurately measured by static method using a DH-1 digital charge meter for the composite diaphragm obtained in the above embodiment and the diaphragm obtained in the comparative example.
[0056] The lithium ion batteries prepared in the examples and comparative examples were subjected to 4-6C charge-discharge cycle test at 25°C and in the range of 20-80% SOC until an inflection point appeared in the discharge capacity decay curve. Lithium deposition occurred at the negative electrode at the inflection point, indicating that the lithium ion battery was failed.
[0057] Table 1. Comparison of piezoelectric properties of PVDF diaphragms and cycle life of lithium-ion batteries in different groups
[0058]
[0059] The specific results are shown in Table 1. Combined with Examples 1-6, it can be seen that within the technical requirements of the present invention, the piezoelectric properties of the PVDF composite diaphragm and the fast-charging cycle life of the lithium-ion battery have been significantly improved, and Example 1 has the best technical effect. Combined with Example 1 and Comparative Examples 1-5, it is shown that the addition of mesocrystalline rutile titanium dioxide powder and MoS2 nanomaterials significantly improves the piezoelectric properties of the PVDF membrane. Compared with conventional diaphragms, the PVDF composite diaphragm with high piezoelectric properties uses the expansion stress of the silicon-based negative electrode to produce a reverse overpotential in a silicon-based system battery, which weakens the probability of lithium precipitation at the interface between the negative electrode and the diaphragm. The lithium precipitation inflection point appears later, which improves the cycle life of the lithium-ion battery under fast charging and significantly reduces the safety risk of the lithium-ion battery under fast charging. At the same time, the mesocrystalline rutile titanium dioxide material provides more lithium storage sites, further improving the cycle life of the battery. The method of the present invention is also applicable to the performance improvement of high-energy-density metal lithium batteries, and provides a technical reference for the development of fast-charging lithium-ion power batteries in fields such as electric aviation.
[0060] It should be noted that the preparation of mesocrystalline anatase titanium dioxide powder requires strict control of parameters as described below. First, a certain amount of titanium source is dripped into 1-3 mol / L hydrochloric acid, wherein the volume ratio of titanium source to hydrochloric acid is 1-3:4-10, and the titanium source used includes but is not limited to dichlorodipentadienyl titanate, tetraisopropoxytitanium, tetrabutyl titanate, titanium citrate, titanium tetrachloride, etc. Then continue stirring at 40-100 ° C for 40-60 hours, centrifuge to obtain a white product, and wash with deionized water 3-6 times to remove residual non-polar ions. After the white product is vacuum dried at 80-120 ° C for 12-36 hours, it is continued to be calcined in air at 400-500 ° C for 12-24 hours to obtain mesocrystalline anatase titanium dioxide powder. Compared with conventional nano- and micron titanium dioxide materials, the synergistic effect of the inherent intergranular rapid diffusion network inside the mesocrystalline anatase TiO2 makes its lithium ion diffusion rate higher and can significantly improve the cycle stability of the material. The mesogenic anatase TiO2 prepared by the present invention includes but is not limited to pure titanium dioxide and its doped and modified derivatives (including nitrogen doping, carbon doping, sulfur doping, various metal and oxide modifications, etc.).
[0061] The preparation of MoS2 nanomaterials requires strict control of the following parameters: add ammonium molybdate and gluconic acid to deionized water in a molar ratio of 0.5-1.5:4-7, stir magnetically at room temperature until dissolved, continue stirring at 110-140°C for 40-60 minutes, stir the white suspension continuously and reflux, add ammonia water to adjust the pH value to 3.5-4.5, then add ammonium polysulfide dropwise to the solution, the molar ratio of ammonium molybdate to ammonium polysulfide is 0.5-1.5:0.7-1.9, finally transfer the solution to a stainless steel autoclave, keep the autoclave at 185-200°C for 12-16 hours, cool naturally to room temperature, centrifuge the solution to obtain a black precipitate MoS2, and rinse with acetone and deionized water three times each to remove the residue. Among them, ammonium molybdate can be replaced by ammonium heptamolybdate tetrahydrate, gluconic acid can be replaced by organic acids such as citric acid, malic acid, and lactic acid, and ammonium polysulfide can be replaced by thiourea, ammonium sulfide, etc. The MoS2 nanomaterial prepared in the present invention can be replaced by one or more other MX2 type semiconductor materials (M is a transition metal element W or Mo, and S is Te, Se or S).
[0062] Those skilled in the art should understand that the positive electrode active material, conductive binder PVDF and N-methylpyrrolidone (NMP) used in the preparation of the positive electrode sheet are put into a ball mill according to a mass ratio of 90-97:0.5-3:1-3:130-160, the ball-to-material ratio is 1.2-1.7:0.9-1.1, and the grinding time is 40min-60min. The mixed slurry is evenly coated on the aluminum current collector by a scraper method or a transfer coating method, and the coating thickness is 50μm-300μm. The positive electrode sheet is obtained after drying, rolling and punching.
[0063] The positive electrode active materials in this embodiment include but are not limited to lithium iron phosphate, layered nickel cobalt manganese ternary materials, lithium cobalt oxide, lithium manganese oxide, lithium iron manganese phosphate, layered lithium-rich manganese base and other positive electrode materials currently available in lithium ion batteries. Positive electrode conductive agents include but are not limited to conductive carbon black, conductive graphite, carbon nanotubes, Ketjen black, graphene and other conductive agents for lithium ion batteries. Positive electrode binders include but are not limited to polyvinylidene fluoride PVDF, sulfated polysaccharides, polytetrafluoroethylene PTFE, polyvinyl alcohol PVA, polyolefins (PP, PE and other copolymers), etc. The positive electrode homogenization process includes but is not limited to ball milling, dry mixing, wet homogenization and all other processes applied to lithium ion positive electrode homogenization; the positive electrode coating process in the present invention includes but is not limited to transfer coating, doctor blade method, extrusion coating, dry electrode and all other lithium ion battery coating processes. The aluminum current collector can be replaced by one of a composite current collector, a carbon-coated aluminum foil, a conductive polymer film, etc.
[0064] Those skilled in the art should understand that the silicon-based materials, graphite, conductive agent, binder and deionized water used in the preparation of the negative electrode sheet are put into a ball mill according to a mass ratio of 50-100: 0-50: 1-10: 2-10: 300-500, the ball-to-material ratio is 1.2-1.7: 0.9-1.1, the grinding time is 50-80 minutes, and the mixed slurry is evenly coated on the copper current collector by a scraper method or a transfer coating method, and the coating thickness is 50-300μm. After drying, rolling and punching, the negative electrode sheet is obtained. Among them, silicon-based materials include but are not limited to silicon oxide, silicon carbon or silicon alloy. Graphite includes but is not limited to natural graphite, artificial graphite, hard carbon, soft carbon, mesophase carbon microspheres, etc. Negative electrode conductive agents include but are not limited to conductive carbon black, conductive graphite, carbon nanotubes, Ketjen black, graphene and other conductive agents for lithium-ion batteries. Negative electrode binders include but are not limited to styrene-butadiene rubber SBR, carboxymethyl cellulose and its derivatives, polyacrylic acid PAA, polyacrylonitrile PAN and other lithium-ion battery negative electrode binders. Negative electrode homogenization processes include but are not limited to ball milling, dry mixing, wet homogenization and all other lithium-ion negative electrode homogenization processes. Negative electrode coating processes include but are not limited to transfer coating, doctor blade method, extrusion coating, dry electrode and all other lithium-ion battery coating processes. The copper current collector can be replaced by one of a composite current collector, a carbon-coated copper foil, a conductive polymer film and the like.
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for manufacturing a high-safety fast-charging lithium battery separator, characterized in that: Mesocrystalline anatase titanium dioxide powder, MX2 semiconductor nanomaterials and PVDF are added to a polar solvent in a molar ratio of 0.3-0.7:0.2-0.5:1.5-1.9, stirred at room temperature and ultrasonically treated in sequence, and then the mixed solution is cast on an ITO conductive glass substrate, and then vacuum dried at 60°C-80°C to form a TiO2-MX2-PVDF composite film, and then gold is sprayed on the surface of the film. Finally, the gold-sprayed TiO2-MX2-PVDF composite film is polarized, with an applied voltage range of 3V-9V and a frequency of 3mS-5mS, to prepare a β-phase-based TiO2-MX2-PVDF composite diaphragm.
2. The method for manufacturing a high-safety fast-charging lithium battery diaphragm according to claim 1, characterized in that: In the MX2 type semiconductor nanomaterial, M is a transition metal element W or Mo, and X is one of Te, Se and S.
3. The method for manufacturing a high-safety fast-charging lithium battery separator according to claim 1, characterized in that: The thickness of the TiO2-MX2-PVDF composite film after vacuum drying is 1μm-15μm, and the thickness of the gold spraying is 5nm-10nm.
4. The method for manufacturing a high-safety fast-charging lithium battery separator according to claim 1, characterized in that: The polar solvent includes one of dimethylformamide DMF, dimethylacetamide DMA, hexamethylphosphoramide, trifluoroacetic acid, tetramethylethylenediamine, pyridine and dimethyl sulfoxide.
5. The method for manufacturing a high-safety fast-charging lithium battery separator according to claim 1, characterized in that: The mesocrystalline anatase titanium dioxide powder is prepared by the following method: a titanium source is dissolved in a 1mol / L-3mol / L hydrochloric acid solution, the volume ratio of the titanium source to the hydrochloric acid solution is 1-3:4-10, the mixture is stirred at 40°C-100°C for 40h-60h, and a white product is obtained by centrifugation. The white product is washed with deionized water to remove residual inorganic ions, and the white product is vacuum dried at 80°C-120°C for 12h-36h, and finally calcined in air at 400°C-500°C for 12h-24h to obtain the mesocrystalline anatase titanium dioxide powder.
6. The method for manufacturing a high-safety fast-charging lithium battery separator according to claim 5, characterized in that: The titanium source includes at least one of titanocene dichloride, tetraisopropoxytitanium, tetrabutyl titanate, titanium citrate, and titanium tetrachloride.
7. The method for manufacturing a high-safety fast-charging lithium battery separator according to claim 1, characterized in that: The MX2 type semiconductor nanomaterial is MoS2 nanomaterial, which is prepared by a solvothermal method: ammonium molybdate or ammonium heptamolybdate tetrahydrate and an organic acid are added to deionized water in a molar ratio of 0.5-1.5:4-7, and magnetic stirring is performed at room temperature until dissolved, and stirring is continued at 110-140°C. The white suspension is continuously stirred and refluxed, and ammonia water is added to adjust the pH value to 3.5-4.5, and then one of ammonium polysulfide, thiourea, and ammonium sulfide is added dropwise to the solution, and finally the solution is transferred to a stainless steel autoclave, the autoclave is kept at 185°C-200°C for a period of time, and naturally cooled to room temperature, and the solution is centrifuged to obtain a black precipitate MoS2, which is rinsed with acetone and deionized water in turn to remove residues.
8. The method for manufacturing a high-safety fast-charging lithium battery separator according to claim 7, characterized in that: The molar ratio of the ammonium molybdate to the ammonium polysulfide is 0.5-1.5:0.7-1.
9.
9. The method for manufacturing a high-safety fast-charging lithium battery separator according to claim 7, characterized in that: The organic acid is one of gluconic acid, citric acid, malic acid and lactic acid.
10. A high-safety fast-charging lithium battery, characterized in that: The invention comprises a diaphragm prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Diaphragm for lithium ion battery as well as preparation method and application of diaphragm
CN117832754A
Lithium-sulfur battery diaphragm and preparation method thereof
CN108511664A
Lithium ion battery molybdenum disulfide titanium dioxide negative electrode material, and preparation method and application thereof
CN112290003A